Cardiac function and autonomic cardiac function during a multi-stage cycling event: a brief report - Menard, Vincent; Barrero, Anna; Lachard, Thibault; Robinault, Lucien; Li, Lingxia; Schnell, Frederic; Carré, François; Le Douairon Lahaye, Solène (Frontiers in Sports and Active Living, 2024)
Introduction Prolonged and repeated exercise performed during an ultra-endurance event can induce general and cardiac fatigue known as exercise-induced cardiac fatigue. Our objective was to find a possible correlation between the cardiac function and the autonomic cardiac function. Methods During a multistage ultra-endurance event, a female well-trained cyclist underwent daily rest echocardiography and heart rate variability measurements to assess the cardiac function and the cardiac autonomic function. Results The athlete completed 3,345 km at 65% of her maximum heart rate and 39% of her maximum aerobic power. A progressive improvement of the systolic function for both the left ventricle and the right ventricle was observed during the event. Discussion Alterations were observed on the cardiac autonomic function with an imbalance between sympathetic and parasympathetic, but there was no sign of a significant correlation between the cardiac function and the autonomic cardiac function and no signs of cardiac fatigue either. Further analysis should be performed on a larger sample to confirm the obtained results.